Development of alkali activated borosilicate inorganic polymers (AABSIP) - Williams, Ross; van Riessen, Arie (Elsevier Science, 2011)
A new class of materials is presented namely, alkali activated borosilicate inorganic polymers (AABSIP), which are similar to alkali activated aluminosilicate polymers (geopolymers). The pastes made with this new material (Na1.10BSi1.70O8.88·4.65(H2O)) were found to have a compressive strength of up to 56(7) MPa and a Young’s modulus of 1.95(7) GPa. The microstructure is composed of a glassy matrix with many sub micron pores with some remnant precursor material. The AABSIP materials have been identified as suitable for structural and non-structural applications, particularly neutron shielding.